Challenges for Financing Startups in China: A Quantitative Investigation of Small and Medium Ventures - Pallathadka, Harikumar (Integrated Journal for Research in Arts and Humanities, 2022)
This research aims to determine the financial obstacles startups face in China. This study will analyze the many different kinds of obstacles that young businesses in China face, and it will also talk about the financial resources that are accessible to young businesses in China. Both topics will be covered in this study. The literature reviewed for this research examines the various difficulties faced by startup businesses from three different vantage points. These are the ailment of venture capital (VC), the difficulties associated with finance for small and medium-sized businesses (SMEs), and the financial issues faced by startup businesses in China. The rapid expansion of new businesses in China has the potential to significantly impact the country's ambitions to become a world leader in scientific discovery and technological innovation. This research also attempts to discover some answers for the new businesses just starting up in China to inspire more young people to get into business for themselves. This article discusses startup firms' financial challenges and the primary financial resources available to them. In order to learn about the elements that affect the difficulties associated with startup funding in China, a survey was conducted with a sample size of 218 participants. According to the research findings, the elements that assist in determining the difficulties associated with funding new businesses in China include the availability of financial resources, support systems and workforces, knowledge, and experience.